Dear colleague : common and uncommon observations - Tuan, Yi-fu, 1930-2022 (University of Minnesota Press, 2002)
Maybe the most influential scholar youve never heard of was how a feature article in The Chronicle of Higher Education recently described Yi-Fu Tuan, a widely traveled Chinese-American geographer whose letters to his friends and colleagues, distilling observations, ideas, and experiences, have carried his insights, and his reputation, far beyond his chosen field. Culling the most characteristic thoughts and compelling moments from these prized letters, Dear Colleague at long last gives readers near and far the opportunity to share what Tuans correspondents have already enjoyed.